2009
DOI: 10.1007/s00284-009-9445-4
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal Diversity in Deep-Sea Sediments Estimated by Means of Different Terminal-Restriction Fragment Length Polymorphisms (T-RFLP) Protocols

Abstract: Despite the increasing recognition of the quantitative importance of Archaea in all marine systems, the protocols for a rapid estimate of Archaeal diversity patterns in deep-sea sediments have been only poorly tested yet. Sediment samples from 11 deep-sea sites (from 79 degrees N to 36 degrees N, at depths comprised from 469 to 5,571 m) were used to compare the performance of two different primer sets (ARCH21f/ARCH958r and ARCH109f/ARCH 915r) and three restriction enzymes (AluI, Rsa I, and HaeIII) for the fing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
(39 reference statements)
0
13
1
Order By: Relevance
“…Recently, Mediterranean-specific archaeal “ecotypes” were identified in bathypelagic waters [99], while fingerprinting analyses to determine benthic archaeal OTU richness reported a diversity roughly 10 times lower than that for Bacteria (range 3–35 OTUs per gram of sediment; [100]). As in the case of bacterial assemblages, the composition of Mediterranean archaeal assemblages is significantly different from that of deep Atlantic sediments [100]. Interestingly, significant longitudinal differences could be observed between the Western, Central, and Eastern Mediterranean, with a turnover diversity reaching 99%, indicating high regional variability [95].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Mediterranean-specific archaeal “ecotypes” were identified in bathypelagic waters [99], while fingerprinting analyses to determine benthic archaeal OTU richness reported a diversity roughly 10 times lower than that for Bacteria (range 3–35 OTUs per gram of sediment; [100]). As in the case of bacterial assemblages, the composition of Mediterranean archaeal assemblages is significantly different from that of deep Atlantic sediments [100]. Interestingly, significant longitudinal differences could be observed between the Western, Central, and Eastern Mediterranean, with a turnover diversity reaching 99%, indicating high regional variability [95].…”
Section: Resultsmentioning
confidence: 99%
“…Prokaryotic diversity has been investigated using molecular approaches that include a wide range of techniques, among them fingerprinting methods such as ARISA or T-RFLP, which reflect the richness and community composition of the dominant components of the assemblage in large sets of samples [88], [100], [265] and the cloning and sequencing of 16S rRNA genes, which also provide information on the phylogenetic identity of dominant members [96], [193]. ARISA and T-RFLP analyses were carried out as described, respectively, by Danovaro et al [97] and Luna et al [88], [100].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of clone sequences with T-RFLP (Table S1, supplementary material) indicate that not all T-RFLP OTUs are represented in the library. A bias of the Archaea-specific primer pair used against the documented methanogenic Archaea is unlikely, as amplification of a wide range of methanogens is generally achieved with this primer set [21,32,33,63], and e.g., Methanosarcina was readily amplified as a positive control by the PCR reaction.…”
Section: Environmental Euryarchaeotamentioning
confidence: 99%
“…Among these, bacteria and archaea have been studied in detail (Stackebrandt et al 1993;Urakawa et al 1999;Li et al 1999;Takai and Horikoshi 1999;DeLong and Pace. 2001;Sogin et al 2006;Hongxiang et al 2008;Luna et al 2009). A few recent studies have reported eukaryotic diversity from extreme environments such as hydrothermal vents (López-García et al 2003, anoxic environments Jebaraj et al 2010) and deep-sea sediments (Bass et al 2007;Edgcomb et al 2011).…”
Section: Introductionmentioning
confidence: 97%